2016
DOI: 10.1021/acs.jpcc.6b04714
|View full text |Cite
|
Sign up to set email alerts
|

Chain-Assisted Charge Transport in Semicrystalline Conjugated Polymers

Abstract: Charge-carrier transport in a paradigmatic semicrystalline polymer semiconductor (P3HT) is important for both fundamental understanding and applications. In samples with enhanced structural disorder due to ad-hoc point defects, the mobility displays rich behavior as a function of electric field (F) and temperature (T ). At low T , the mobility increases with the applied field but upon further increasing T, the field-dependence becomes shallower. Eventually, at the highest T considered, the slope changes sign a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Consistent with previous studies, 1719 the differences in mobility likely lie in the way the polymers pack together and the electronic coupling between the chains in the bulk. This coupling can only be assessed with precise geometrical information on the relative distances, orientation and translations between chains; information that is not available at this point in time.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, 1719 the differences in mobility likely lie in the way the polymers pack together and the electronic coupling between the chains in the bulk. This coupling can only be assessed with precise geometrical information on the relative distances, orientation and translations between chains; information that is not available at this point in time.…”
supporting
confidence: 89%
“…16 In the case of hopping transport in disordered systems, the interchain ordering, or morphology, is a deterministic factor that limits transport. 1719 Electron–phonon coupling determining the reorganization energies for single electron-transfer events may be a lesser factor, however, its role nevertheless needs to be clarified in relation to the regiochemistry at a single polymer chain level. Moreover, reorganization energies along with electronic couplings provide the necessary microscopic input into theoretical global dispersive transport simulations provided that the morphology of the materials is well understood.…”
mentioning
confidence: 99%
“…Therefore, charge transport along polymer chains, called intrachain transport, is faster than charge transport between two separate polymer chains, which we refer to as inter-chain transport [51][52][53]. Vanlaeke et al showed that crystallization of P3HT increases the mobility [54].…”
Section: Polymer Chainsmentioning
confidence: 98%
“…While for some devices such as OLEDs, a low mobility is critical to optimize the performance, OSCs and OTFTs demand a high mobility. In semiconducting polymers, charge carrier mobility strongly depends on the morphology [54,55], but its interplay is not well understood [52,96]. Investigating the impact of different transport mechanisms, such as intrachain hopping, on carrier mobility can help the development of organic materials and improve device performance.…”
Section: Charge Carrier Transport Through Polymer Chainsmentioning
confidence: 99%
“…Besides the elucidation of mechanical response and polymer dynamics at the molecular scale, another application could be the identification of the pathways taken by charges in semiconducting polymer materials for solar cells, where the charge mobility is linked in a non-trivial way to the macromolecule conformation. 11 However, challenges both in the implementation of this method and in the method itself remain; for example, chemical inhomogeneity in the polymeric force sensors leads to signal broadening. Improvement of the synthetic protocols would enable a more fine-tuned detection of forces in which the artificial signal due to chemical heterogeneity is suppressed.…”
mentioning
confidence: 99%